Penyuluhan hukum tentang pentingnya pendaftaran tanah di Desa Empus Kecamatan Bahorok Kabupaten Langkat - Maswita, Maswita; Khairiah, Umi; Sipahutar, Anjani; Rigitta, Prinsi; Ramadhan, Andri (LPPM Universitas Al-Azhar medan, 2025)
The use of internet technology today has resulted in the dissemination of information in all fields easily and quickly globally. One thing that plays a role in this is translation activities, which allow information to be shared in different languages. Translation is an activity and product that is very important for anyone who eager know or introduce things belonging to a group, culture or nation to others. Learning to translate starts from the initial phase of learning a foreign language, but the translation ability is not automatically obtained by mastering a foreign language. Considering that translation is a potential field for the translator profession, the younger generation, especially students majoring in translation, need to be motivated to work in the field of translation which is beneficial to support their achievements in academics as well as in their careers and professional lives in the future..